Diabetes and Chronic Pancreatitis: Considerations in the Holistic Management of an Often Neglected Disease - Philip C. Johnston; Judith Thompson; Allison Mckee; Connor Hamill; Ian Wallace (Journal of Diabetes Research)
Diabetes secondary to chronic pancreatitis (CP) or type 3cDM refers to a brittle form of diabetes and is often characterised by hypoglycaemic episodes, erratic glycaemic control, and impaired quality of life. It differs from other forms of diabetes and is typically characterised by concurrent pancreatic endocrine and exocrine insufficiency which can present as malabsorption and nutritional deficiencies. In this review, we discuss the pathogenesis, epidemiology, and the practicalities of diagnosis, screening, and management of this condition.